2015
DOI: 10.1504/ijcaet.2015.068334
|View full text |Cite
|
Sign up to set email alerts
|

An exact algorithm for the full truckload pick-up and delivery problem with time windows: concept and implementation details

Abstract: Intermodal goods transport is characterized by a main transport by rail, barge or seaborne vessel, preceded and followed by short in time but expensive road transport. Many times trucks pick-up or deliver a single container which leads to a full truckload vehicle routing problem in terms of economically efficient transport services. Time windows induced by the customer or due to external situations increase the complexity of an efficient planning by a logistics provider. An exact algorithm for this type of pic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…From a practical viewpoint, this case is mostly relevant in container transport, which is abstractly formulated as the full-truckload pick-up and delivery problem (FT-PDPTW) (Erera and Smilowitz, 2008;Janssens and Braekers, 2011). It has been shown that a problem of the type FT-PDPTW can be transformed into an asymmetric multiple travelling salesmen problem Downloaded by [New York University] at 07:09 11 June 2015 with time windows by collapsing each time request into a single node (Wang and Regan, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From a practical viewpoint, this case is mostly relevant in container transport, which is abstractly formulated as the full-truckload pick-up and delivery problem (FT-PDPTW) (Erera and Smilowitz, 2008;Janssens and Braekers, 2011). It has been shown that a problem of the type FT-PDPTW can be transformed into an asymmetric multiple travelling salesmen problem Downloaded by [New York University] at 07:09 11 June 2015 with time windows by collapsing each time request into a single node (Wang and Regan, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%